Causes and consequences of variation in leaf mass per area (LMA) a meta-analysis - Poorter, Hendrik (The New phytologist, 2009)
Here, we analysed a wide range of literature data on the leaf dry mass per unit area (LMA). In nature, LMA varies more than 100-fold among species. Part of this variation (c. 35%) can be ascribed to differences between functional groups, with evergreen species having the highest LMA, but most of the variation is within groups or biomes. When grown in the same controlled environment, leaf succulents and woody evergreen, perennial or slow-growing species have inherently high LMA. Within most of the functional groups studied, high-LMA species show higher leaf tissue densities. However, differences between evergreen and deciduous species result from larger volumes per area (thickness). Response curves constructed from experiments under controlled conditions showed that LMA varied strongly with light, temperature and submergence, moderately with CO2 concentration and nutrient and water stress, and marginally under most other conditions. Functional groups differed in the plasticity of LMA to these gradients. The physiological regulation is still unclear, but the consequences of variation in LMA and the suite of traits interconnected with it are strong. This trait complex is an important factor determining the fitness of species in their environment and affects various ecosystem processes